Germinal GLT8D1, GATAD2A and SLC25A39 mutations in a patient with a glomangiopericytal tumor and five different sarcomas over a 10-year period - Beddok, Arnaud (Sci Rep, 2021)
Soft tissue sarcoma represents about 1% of all adult cancers. Occurrence of multiple sarcomas in a same individual cannot be fortuitous. A 72-year-old patient had between 2007 and 2016 a glomangiopericytal tumor of the right forearm and a succession of sarcomas of the extremities: a leiomyosarcoma of the left buttock, a myxofibrosarcoma (MFS) of the right forearm, a MFS of the left scapula, a left latero-thoracic MFS and two undifferentiated sarcomas on the left forearm. Pathological examination of the six locations was not in favor of disease with local/distant recurrences but could not confirm different diseases. An extensive molecular analysis including DNA-array, RNA-sequencing and DNA-Sanger-sequencing, was thus performed to determine the link between them. The genomic profile of the glomangiopericytal tumor and the six sarcomas revealed that five sarcomas were different diseases and one was the local recurrence of the glomangiopericytal tumor. While the chromosomal alterations in the six tumors were different, a common somatic CDKN2A/CDKN2B deletion was identified. RNA-sequencing of five tumors identified mutations in GLT8D1, GATAD2A and SLC25A39 in all samples. The germline origin of these mutations was confirmed by Sanger-sequencing. Innovative molecular analysis methods have made possible a better understanding of the complex tumorigenesis of multiple sarcomas.